2000
DOI: 10.1089/thy.2000.10.79
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Spot Thyrotropin Method is Not Adequate to Screen for Hypothyroidism in the Elderly Living in Abundant-Iodine Intake Areas: Comparison to Sensitive Thyrotropin Measurements

Abstract: We investigated whether the blood spot thyrotropin (TSH) method was adequate for screening elderly subjects with abundant iodine intake (median excretion 330 microg/g creatinine) for hypothyroidism. In 97 healthy adults (group A), 210 nursing home residents (group B) and 265 elderly subjects living at home (group C) serum (sensitivity < 0.02 mU/L, cost 1.2 U.S. dollars [USD]) and blood spot TSH (sensitivity < 1.0 mU/L, cost 0.4 USD) were measured, and the sensitivity and specificity of different blood spot TSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The pattern of many cases of thyroid hyperfunction in mild or moderate iodine deficiency and many cases of thyroid hypofunction with high iodine intake has been found in many other studies (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Environmental Iodinementioning
confidence: 63%
“…The pattern of many cases of thyroid hyperfunction in mild or moderate iodine deficiency and many cases of thyroid hypofunction with high iodine intake has been found in many other studies (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Environmental Iodinementioning
confidence: 63%
“…Both of these studies therefore support the use of DBS TSH for detecting primary hypothyroidism in adults and children. However, a study by Takáts et al 2000 reported that a high diagnostic sensitivity of 94% for DBS TSH could only be achieved at the expense of a poor specificity of 72%. 27 Future work for us would therefore be to perform a study evaluating the diagnostic potential of the DBS TSH reference interval.…”
Section: Discussionmentioning
confidence: 99%
“…25 When we compared serum and DBS results for 118 patients, only one patient was positive by the serum and negative by the DBS assay. The DBS method used by Takats et al was not described in detail, but the short incubation time suggests that there may have been a problem with extraction of TSH from the lter paper.…”
Section: Discussionmentioning
confidence: 99%
“…24 Iodine-de cient patients with mild hypothyroidism may be missed in adult screening programmes using TSH and might have contributed to the problems with DBS TSH screening reported by Takats et al in a population that may have had iodine de ciency. 25 Screening for thyroid disease in adults can be done accurately with DBS specimens. When specimens were collected simultaneously for serum and DBS testing for 118 individuals, only one specimen was positive by serum and negative by DBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation